Valuing Chaparral Ecological, Socio-Economic, and Management Perspectives (Springer Series on Environmental Management,, 2018)
Chaparral shrubland ecosystems are an iconic feature of the California landscape, and a highly biodiverse yet highly flammable backdrop to some of the fastest growing urban areas in the United States. Chaparral-type ecosystems are a common element of all of the world's Mediterranean-type climate regions - of which California is one - yet there is little public appreciation of the intrinsic value and the ecosystem services that these landscapes provide. Valuing Chaparral is a compendium of contributions from experts in chaparral ecology and management, with a focus on the human relationship with chaparral ecosystems. Chapters cover a wide variety of subjects, ranging from biodiversity to ecosystem services like water provision, erosion control, carbon sequestration and recreation; from the history of human interactions with chaparral to current education and conservation efforts; and from chaparral restoration and management to scenarios of the future under changing climate, land use, and human population. Valuing Chaparral will be of interest to resource managers, the research community, policy makers, and the public who live and work in the chaparral dominated landscapes of California and other Mediterranean-type climate regions.